Limitation of the Authority Constitutional Court in Forming Legal Norms on the Testing of Laws Against the 1945 Constitutional Law of the Republic Indonesia - Yodika Sputra,; Tomy Michael, (Technium Social Sciences Journal, 2025)
The Constitutional Court is the result of developments in the state system in Indonesia after the renewal of the New Order. The birth of the Constitutional Court is a product of third and fourth amendments to the 1945 Constitution of the Republic Indonesia (hereinafter referred to as the 1945 Constitution of the Republic Indonesia) in 2001-2002. Article 24 paragraph (2) the 1945 Constitution of the Republic Indonesia, reads: "judicial power is exercised by the Supreme Court and judicial bodies under it in the general court environment, the military court environment, the state administrative court environment, and by a Constitutional Court". Based on these provisions, the Constitutional Court is one of actors judicial power in Indonesia besides the Supreme Court. Juridicial review application is an attempt to re-read a legal product that has been formed and ratified by the President as a correction to the legal formation institution (Rustam Rustam, 2022). In other words, the testing carried out by the Constitutional Court can be in the form of material and formal testing. According to Article 2 (3) of the Constitutional Court Regulation Number 2 of 2021 concerning the Procedures for Testing Laws, it reads "formal testing is testing of the process of forming laws or perppu that do not meet the provisions for forming laws or perppu as referred to in the 1945 Constitution", while Article 2 (4), reads "material testing is testing relating the content of material, in paragraphs, articles and/or parts of laws or perpu that are considered to be in conflict with the 1945 Constitution". The addition of new norms in several decisions has caused controversy and concerns about the potential for abuse of power, so that limiting authority is a strategic step to prevent the dominance of the institution. Limiting the Authority of the Constitutional Court is needed to ensure the realization of a balance of power in a system of division of power in Indonesia. The Constitutional Court as part of the perpetrators of power should continue to act as a negative legislator in order to maintain the supremacy of law, the sovereignty of constitutional rights and maintain the principle of checks and balances.